1993
DOI: 10.1243/pime_proc_1993_207_147_02
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Liquid Sloshing in Horizontal Cylindrical Road Containers

Abstract: A study of the liquid behaviour in horizontal cylindrical road containers undergoing a steady turning manoeuvre is presented and discussed. The steady state solutions are derived analytically from the hydrostatic equations. The transient solutions are obtained by numerical integration of the Navier-Stokes, continuity and free-surface equations. The non-dimensional governing equations are solved in primitive variables by using a modified marker-and-cell technique which involves the interpolation-reflection type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 3 publications
6
27
0
3
Order By: Relevance
“…Therefore, the liquid in the model absorber need only have the same density as the liquid in the prototype and a viscosity low enough to give a Reynolds number of greater than 10. This conclusion is in close agreement with observations given by Popov et al [18] for liquid sloshing in horizontal cylindrical road containers. Popov et al showed viscosity had no e!ect for Re in the range 10}10, and the e!ect was small for Re in the range 10}10.…”
Section: On Practical Applicationsupporting
confidence: 94%
“…Therefore, the liquid in the model absorber need only have the same density as the liquid in the prototype and a viscosity low enough to give a Reynolds number of greater than 10. This conclusion is in close agreement with observations given by Popov et al [18] for liquid sloshing in horizontal cylindrical road containers. Popov et al showed viscosity had no e!ect for Re in the range 10}10, and the e!ect was small for Re in the range 10}10.…”
Section: On Practical Applicationsupporting
confidence: 94%
“…Tank trucks are frequently subjected to steering and braking-induced accelerations, while carrying partially filled liquid tanks. The resulting fluid movements within the tank yield additional forces and moments imposed on the vehicle, which affect the braking performance and roll stability limits of the vehicle in an adverse manner [1][2][3]. On the basis of the reported highway accidents involving heavy vehicles, it has been suggested that tank trucks are 4.8 times more * likely to be involved in rollover accidents than the rigid cargo vehicles [4].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated the dynamic fluid slosh within cylindrical and rectangular containers subject to acceleration fields in either roll or pitch planes [3,7,8]. These studies have derived forces and moments caused by fluid slosh under either a lateral or longitudinal acceleration, whereas only a single study has attempted to study the lateral dynamics of a partlyfilled tank truck subject to lateral force and roll moment due to dynamic fluid slosh [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, only liquid sloshing in a few tanks could be solved using this method. [9][10][11] 2. The computational fluid dynamics (CFD) method.…”
Section: Introductionmentioning
confidence: 99%